Role of nutraceutical- branched chain amino acids for attenuating skeletal muscle soreness in post exercise status and central fatigue - Deo, Satish Kumar; Pokharel, Akritee; Lamichhane, Samir; Mudvari, Anish (Journal of Chitwan Medical College, 2017)
Implementation of food extract for target medicinal purpose is a genre in medical science called Nutraceutical which is vast and much of it is yet to be explored. Nowadays general population are aware of the importance of exercise in terms of health benefits but the fatigue and delayed onset muscle soreness (DOMS) are limitations that are to be overcome to continue extensive exercises. For this article, the role of Branched chain amino acids (BCAA) for the purpose is studied from various scientific journal. DOMS is due to direct muscle damage following exercise whereas central fatigue is the sensation of fatigue due to neurochemical changes in brain following exercise. In various studies, DOMS and central fatigue were minimized in terms of duration when given to animals and human volunteers. Further research has to be done regarding dosing regimen of BCAA supplementation and also to uncover any adverse effect of the supplements.